2017
DOI: 10.3727/096504016x14719078133564
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sensitivity Predictors of Neoadjuvant Chemotherapy for the Treatment of Adenocarcinoma of Gastroesophageal Junction

Abstract: The identification of reliable predictors of chemotherapy sensitivity and early screening of adenocarcinoma of gastroesophageal junction (AGEJ) patients who are resistant to chemotherapy has become an important area of clinical and translational research. We aimed to investigate the predictive value of seven cancer-associated cellular proteins for neoadjuvant chemotherapy in AGEJ patients. Clinical data of 93 patients who received neoadjuvant chemotherapy for locally advanced AGEJ between June 2010 and Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…In our analysis of the biopsy cohort before CTx treatment, we did not find an association with response to therapy in terms of tumor regression or with respect to the survival of the patients. This is in line with a report analyzing only a small number of pretherapeutic tumor biopsies [24], whereas other studies reported that mutated or aberrant expression of p53 indicated chemoresistance [25][26][27]. These inconsistent results may be due to various reasons related to the complexity and functional diversity of p53 and p53 mutations, as well as to differences in the applied chemotherapeutic regimens and in patient characteristics, while methodical aspects of p53 determination most likely play a role.…”
Section: Discussionsupporting
confidence: 80%
“…In our analysis of the biopsy cohort before CTx treatment, we did not find an association with response to therapy in terms of tumor regression or with respect to the survival of the patients. This is in line with a report analyzing only a small number of pretherapeutic tumor biopsies [24], whereas other studies reported that mutated or aberrant expression of p53 indicated chemoresistance [25][26][27]. These inconsistent results may be due to various reasons related to the complexity and functional diversity of p53 and p53 mutations, as well as to differences in the applied chemotherapeutic regimens and in patient characteristics, while methodical aspects of p53 determination most likely play a role.…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, in the cases of breast cancer, a high Ki-67 LI value is associated with higher response rate to chemotherapy, as seen in the neoadjuvant treatment arm [1819]. Moreover, Li et al [20] recently reported that gastroesophageal cancer showed good response to chemotherapy in cases with elevated Ki-67 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are still some patients with the same TNM stage and different prognosis [ 10 ]. Although a few of molecular markers are identified to stratify survival in different cohorts of GC patients [ 11 14 ], simple, inexpensive, and valid signatures to generate prognostic model are still unavailable at clinical settings.…”
Section: Introductionmentioning
confidence: 99%